PROSES PENYELESAIAN PERKARA PEMBATALAN PERKAWINAN KARENA TIDAK ADANYA IZIN POLIGAMI - Susanto Susanto (SOL JUSTICIA, 2019)
This study aims to find out how the process of settling marital cancellations is due to the absence of a polygamy permit and what are the judges' considerations in the marriage cancellation case. This research is a normative legal research that is prescriptive and technical or applied. The research approach uses the law approach and case approach. The type of research data is secondary data with primary and secondary legal materials. Data collection techniques such as literature study and data analysis techniques used are deductive. The results of this study explain that the Compilation of Islamic Law also regulates everything related to marriage, in the case of the cancellation of this marriage the legal basis is article 71 (a), (e), and (f) Compilation of Islamic Law in which these laws and regulations have been emphasize it, so that this marriage can be null and void by law and the cancellation of the marriage of the parents does not apply retroactively to the child they are born with. That means, even though the child is the result of an unmarried marriage, the child is still referred to as a legitimate child, while the only thing that is nullified is the marriage bond. children can be considered as legitimate children or not if viewed in terms of gestational age until delivery, whether it has reached 180 days / 6 months.